Robot assisted radical cystectomy with Florence robotic intracorporeal neobladder (FloRIN): Analysis of survival and functional outcomes after first 100 consecutive patients upon accomplishment of phase 3 IDEAL framework. Issue 10 (October 2021) - Minervini, Andrea; Di Maida, Fabrizio; Tasso, Giovanni; Mari, Andrea; Bossa, Riccardo; Sforza, Simone; Grosso, Antonio Andrea; Tellini, Riccardo; Vittori, Gianni; Siena, Giampaolo; Tuccio, Agostino; Masieri, Lorenzo; et al.
Abstract: Introduction: Aim of the study was to evaluate the Florence intracorporeal neobladder (FloRIN) oncological and functional outcomes at the end of assessment phase (phase 3) IDEAL-Guidelines. Materials and methods: This single-institution prospective series included consecutive patients treated with robot-assisted radical cystectomy (RARC) and FloRIN reconfiguration technique from February 2016 to June 2020. Functional features were evaluated six months after surgery. Patients were grouped into four quartiles according to time of radical cystectomy and impact of learning curve improvement was evaluated. Results: One-hundred FloRIN were completed with a median console time of 373 (IQR: 312–415) minutes. Two cases were converted to open surgery. No intraoperative complications occurred. At pathological examination, 30% of patients were staged as pT ≤ 1 and 47% as pT ≥ 3. Transitional cell carcinoma was present in 87% of cases. Carcinoma in situ (CIS) and nodal involvement were observed in 38% and 29% of patients, respectively. At a median follow-up time of 17 (IQR: 7–28) months, 20 clinically relevant events (Clavien-Dindo≥3) occurred. Operative time significantly decreased throughout the series (median minutes 435; 395; 365 and 330 in the four quartiles, respectively; p < 0.001). Similarly, early Clavien-Dindo≥3 postoperative complications rate significantly decreased across the series (number of events: 1; 4; 0; 0; p = 0.03). Overall, 75% and 65% of patients achieved day-time and nigh-time continence, respectively. Twenty-seven patients experienced disease recurrence. Cancer-specific and overall survival were equal to 80%. Conclusions: RARC with FloRIN reconfiguration showed worthy functional and survival outcomes, with learning curve improvement significantly influencing operative time and early complications rate across series.